Pemanfaatan Ulat Sutra di Renggeang dan Tamamangalle Kapupaten Polewali Mandar - Julianto; Ritabulan; Kasmiati (Program Studi Kehutanan Fakultas Pertanian dan Kehutanan Universitas Sulawesi Barat, 2025)
Mandar Silk Sarong is one of the derivative products of NTFPs utilized by the community in Polewali Mandar Regency. The indication of the imbalance between the supply of raw materials and the needs of silk cloth production is the background for the importance of this study. This study aims to describe the existing conditions of the utilization of NTFPs of silkworms and identify the upstream and downstream relationships in the utilization of NTFPs of silkworms in Balanipa and Limboro Districts, Polewali Mandar. Data collection was carried out through observation, interviews and documentation studies. Data analysis used qualitative and quantitative descriptive approaches. The results of the study showed that the relationship between upstream and downstream utilization of NTFPs of silkworms in Limboro and Balanipa Districts, Polman Regency faced a number of obstacles so that it had not been properly established.